International Bureaucracy
XV, 210 p. 5 illus.
Keywords: This book applies established analytical concepts such as influence, authority, administrative styles, autonomy, budgeting and multilevel administration to the study of international bureaucracies and their political environment. It reflects on the commonalities and differences between national and international administrations and carefully constructs the impact of international administrative tools on policy making. The book shows how the study of international bureaucracies can fertilize interdisciplinary discourse, in particular between International Relations, Comparative Government and Public Administration. The book makes a forceful argument for Public Administration to take on the challenge of internationalization. Michael W. Bauer is Jean Monnet Professor and holds the chair of Comparative Public Administration and Policy Analysis at the German University of Administrative Sciences in Speyer. Christoph Knill holds thechair of Empirical Theories of Politics at the University of Munich (LMU), Germany, and is the speaker of the research unit ‘International Public Administration’. Steffen Eckhard is Senior Researcher at the University of Munich (LMU), Germany, and a non-resident research fellow at the Global Public Policy Institute in Berlin (GPPi), Germany.